Maternal and Perinatal Health Challenges in Pakistan - Farrukh, Muhammad Junaid; Tariq, Muhammad Haseeb; Shah, Kifayat Ullah (Journal of Pharmacy Practice and Community Medicine)
Dear Editor, Maternal and perinatal mortality have appeared a huge challenge in the health care setting of developing countries. [1] Considering the importance of this issue, in 1987 maternal and perinatal health is considered a priority in the Millennium Development Goals (MDGs). Regrettably, Pakistan is still struggling to meet to the MDGs goal of maternal and child health by 2015.